(untitled) (Anthropos: Jurnal Antropologi Sosial dan Budaya (Journal of Social and Cultural Anthropology), 2020)
The aims of this paper is to explain the use of high heels as an agency for a woman’s body. Agency context refers to pain in the body but pain is perceived as something positive. In this paper, the method used is a literature review by reviewing writings related to the use of high heels. The findings in this paper that women experience body image disturbance or anxiety because they feel themselves are not beautiful or not attractive. The use of high heels, makes women more attractive and more confident, on the other hand the use of high heels actually makes women feel pain and discomfort. However, for the achievement of beauty standards, women voluntarily allow their bodies to experience pain. However, the agency’s willingness to beauty standards here is meaningless without filtering and directly accepted. Instead women keep negotiating with themselves so as to make a decision why use high heels.